2003
DOI: 10.1074/jbc.m301798200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Human BCL-w

Abstract: The structure of human BCL-w, an anti-apoptotic member of the BCL-2 family, was determined by tripleresonance NMR spectroscopy and molecular modeling. Introduction of a single amino acid substitution (P117V) significantly improved the quality of the NMR spectra obtained. The cytosolic domain of BCL-w consists of 8 ␣-helices, which adopt a fold similar to that of BCL-x L , BCL-2, and BAX proteins. Pairwise root meant square deviation values were less than 3 Å for backbone atoms of structurally equivalent region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(32 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…The equivalent hydrogen bond in Mcl-1 would be disrupted, as the corresponding residues are Lys-215 and His-233, respectively, and this may contribute to the open conformation found in Mcl-1⌬NC23. Like Mcl-1, Bcl-w also has ␣3 and ␣4 in an open conformation, but here the C-terminal residues occupy the binding groove and may influence the conformation (23,38). These differences in the binding groove likely contribute to the specific binding properties of Mcl-1.…”
Section: Structural Comparison With Other Bcl-2 Family Members-mentioning
confidence: 99%
“…The equivalent hydrogen bond in Mcl-1 would be disrupted, as the corresponding residues are Lys-215 and His-233, respectively, and this may contribute to the open conformation found in Mcl-1⌬NC23. Like Mcl-1, Bcl-w also has ␣3 and ␣4 in an open conformation, but here the C-terminal residues occupy the binding groove and may influence the conformation (23,38). These differences in the binding groove likely contribute to the specific binding properties of Mcl-1.…”
Section: Structural Comparison With Other Bcl-2 Family Members-mentioning
confidence: 99%
“…Previous structural studies of Bcl-2, Bcl-X L , Bcl-W, and Mcl-1 have been performed using proteins in which the C-terminal membrane-insertion domain was similarly omitted from the recombinant protein. [7][8][9] Proteins were purified by one-step affinity chromatography using glutathione-Sepharose. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis with Coomassie staining demonstrated that the resulting proteins were 485% intact (Figure 1a).…”
mentioning
confidence: 99%
“…Three-dimensional structures of monomeric antiapoptotic proteins such as Bcl-x L , Bcl-2, Bcl-w, and CED-9 as well as proapoptotic proteins such as Bax and Bid have been determined (5)(6)(7)(8)(9)(10)(11)(12). A hydrophobic surface groove common to the structures of all of the antiapoptotic proteins is encircled by five helices (helices 2-5 and 8) and connecting loops.…”
mentioning
confidence: 99%